Epidemiological profile and north–south gradient driving baseline systemic involvement of primary Sjögren's syndrome. (24th December 2019) - Brito-Zerón, Pilar; Acar-Denizli, Nihan; Ng, Wan-Fai; Horváth, Ildiko Fanny; Rasmussen, Astrid; Seror, Raphaele; Li, Xiaomei; Baldini, Chiara; Gottenberg, Jacques-Eric; Danda, Debashish; Quartuccio, Luca; Priori, Roberta; et al.
Abstract: Objective: To characterize the systemic phenotype of primary Sjögren's syndrome at diagnosis by analysing the EULAR-SS disease activity index (ESSDAI) scores. Methods: The Sjögren Big Data Consortium is an international, multicentre registry based on worldwide data-sharing cooperative merging of pre-existing databases from leading centres in clinical research in Sjögren's syndrome from the five continents. Results: The cohort included 10 007 patients (9352 female, mean 53 years) with recorded ESSDAI scores available. At diagnosis, the mean total ESSDAI score was 6.1; 81.8% of patients had systemic activity (ESSDAI score ≥1). Males had a higher mean ESSDAI (8.1 vs 6.0, P < 0.001) compared with females, as did patients diagnosed at <35 years (6.7 vs 5.6 in patients diagnosed at >65 years, P < 0.001). The highest global ESSDAI score was reported in Black/African Americans, followed by White, Asian and Hispanic patients (6.7, 6.5, 5.4 and 4.8, respectively; P < 0.001). The frequency of involvement of each systemic organ also differed between ethnic groups, with Black/African American patients showing the highest frequencies in the lymphadenopathy, articular, peripheral nervous system, CNS and biological domains, White patients in the glandular, cutaneous and muscular domains, Asian patients in the pulmonary, renal and haematological domains and Hispanic patients in the constitutional domain. Systemic activity measured by the ESSDAI, clinical ESSDAI (clinESSDAI) and disease activity states was higher in patients from southern countries ( P < 0.001). Conclusion: The systemic phenotype of primary Sjögren's syndrome is strongly influenced by personal determinants such as age, gender, ethnicity and place of residence, which are key geoepidemiological players in driving the expression of systemic disease at diagnosis.